Analysis and Optimization on Transmission Accuracy of Shoulder Joint Reducer for an Upper Limb Rehabilitation Robot - Zou Shuaidong; Wang Guangjian; Xie Guanghui; Hou Jingming; Yang Renqiang; Sun Fanwei (Jixie chuandong)
Based on the characteristics of high error sensitivity and large load capacity of the shoulder joint of the upper limb rehabilitation robot relative to other joints, an involute planetary reducer with small tooth number difference is applied to its shoulder joint drive in this study. Considering the main factors of transmission errors caused by machining and assembly errors, the analytical calculation model of transmission errors of the planetary reducer with small tooth number difference is established based on the mesh line increment method. From the perspective of statistics, Monte Carlo method is used to analyze the effects of eccentricity error and initial phase on the transmission accuracy of the shoulder joint of upper limb rehabilitation robots. Based on the analytical model of shoulder joint transmission accuracy, the output torque fluctuation caused by transmission error is analyzed and particle swarm optimization algorithm is adopted to optimize transmission accuracy under the condition of constant machining accuracy, so as to improve the output torque fluctuation caused by transmission error of the shoulder joint of the upper limb rehabilitation robot to avoid the secondary injury of the patients.